Production and epitope analysis of monoclonal antibodies against a Rhizobium leguminosarum biovar trifolii strain. - Wright, S F (1990)
Heat-treated cells of Rhizobium leguminosarum biovar trifolii strain 162X95 were used to produce monoclonal antibodies (MAbs). The fusion produced three cross-reactive MAbs and eight MAbs specific for the immunizing strain and a group of five other R. trifolii strains from the same geographic region where 162X95 was isolated (California). Seven MAbs were analyzed by competitive enzyme-linked immunosorbent assay to determine the number of different epitopes detectable on strain 162X95. The results indicated that six MAbs reacted with the same or overlapping epitopes, and the seventh MAb gave inconclusive results.